Authentication of animal fats using direct analysis in real time (DART) ionization-mass spectrometry and chemometric tools - Vaclavik, Lukáš; Hrbek, Vojtěch; Čajka, Tomáš; Rohlik, Bo-Anne; Pipek, Petr; Hajšlová, Jana (Journal of agricultural and food chemistry, 2011)
A combination of direct analysis in real time (DART) ionization coupled to time-of-flight mass spectrometry (TOFMS) and chemometrics was used for animal fat (lard and beef tallow) authentication. This novel instrumentation was employed for rapid profiling of triacylglycerols (TAGs) and polar compounds present in fat samples and their mixtures. Additionally, fat isolated from pork, beef, and pork/beef admixtures was analyzed. Mass spectral records were processed by principal component analysis (PCA) and stepwise linear discriminant analysis (LDA). DART-TOFMS profiles of TAGs were found to be more suitable for the purpose of discrimination among the examined fat types as compared to profiles of polar compounds. The LDA model developed using TAG data enabled not only reliable classification of samples representing neat fats but also detection of admixed lard and tallow at adulteration levels of 5 and 10% (w/w), respectively. The presented approach was also successfully applied to minced meat prepared from pork and beef with comparable fat content. Using the DART-TOFMS TAG profiles of fat isolated from meat mixtures, detection of 10% pork added to beef and vice versa was possible.
Keywords: prasata; diskriminační analýza; řízení kvality; Meat; Swine; Triglycerides; skot; Mass Spectrometry; Fats; triglyceridy; Cattle; zvířata; Animals; Discriminant Analysis; Quality Control; hmotnostní spektrometrie; maso; tuky